Analisis Faktor Yang Mempengaruhi Kebijakan Dividen Pada Perusahaan Manufaktur Periode 2017-2019 - Priskila Gracia; Merry Susanti (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study was to determine the effect of profitability, leverage, liquidity, company size and company growth on dividend policy in manufacturing companies on the Indonesia Stock Exchange for the 2017-2019 period. This research was conducted using 165 samples. This study used secondary data from financial reports on manufacturing companies listed on the IDX for the 2017-2019 period used the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The tool used to collect data in this study was Microsoft Excel 2010 software and the tool used to process data in this study was EViews 10 software. The results of this study indicated that profitability and leverage had a negative effect on dividend policy, company size had a positive effect on dividend policy while liquidity and company growth had no effect on dividend policy. The implication of this research is that investors and potential investors need to understand and pay attention to the effect of profitability, leverage, liquidity, company size and company growth on dividend policy in a company.